Adaptive Educational Resource Management In Remote Schools: A Case Study Of Infrastructure And Ict Challenges At SDN Batu Tunau, Indonesia - Muhammad Yahyadin; Muhammad Ahdar; Rusidah; Ahmad Suriansyah; Aslamiyah (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This research investigates how adaptive educational resource management operates in remote school environments where infrastructure and information and communication technology (ICT) limitations create persistent managerial challenges. Focusing on SDN Batu Tunau, a public elementary school located on an island in South Kalimantan, Indonesia, the study explores the strategies administrators employ to sustain educational operations under physical and digital isolation. Using a qualitative descriptive case-study approach, data were collected through semi-structured interviews, field observations, and document analysis. The findings indicate that managerial functions are constrained by two critical external barriers: the physical inaccessibility of the school and the unreliability of internet connectivity. These barriers undermine logistical efficiency, routine maintenance, and digital administration such as Dapodik data reporting and ANBK assessment preparation. Nevertheless, the school demonstrates a form of reactive adaptive management characterized by local innovation, community collaboration, and an “offline-first” orientation in administrative and instructional processes. The study advances the theoretical understanding of adaptive management in education by framing it as a dual-layered system that links internal responsiveness to external policy environments. The paper concludes with practical and policy recommendations for strengthening infrastructure equity and managerial capacity in rural and island schools.